Comparative chloroplast genomes of Argentina species: genome evolution and phylogenomic implications - Li, Qin-Qin; Zhang, Zhi-Ping; Aogan,; Wen, Jun (Frontiers in Plant Science, 2024)
The genus Argentina Hill belongs to the tribe Potentilleae Sweet and contains approximately 75 species predominantly distributed in the Sino-Himalayan region and the Malesian archipelago. So far we have less knowledge on the phylogenetic relationships within Argentina owing to limited sampling of Argentina taxa or gene fragments in previous studies. Moreover, to date there is no phylogenetic study on Argentina from the perspective of comparative chloroplast (cp) genomics. Here we performed comparative genomic analyses on the cp genomes of 39 accessions representing 18 taxa of Argentina. The Argentina cp genomes presented the typical quadripartite structure, with the sizes ranging from 155 096 bp to 157 166 bp. The 39 Argentina cp genomes contained a set of 112 unique genes, comprising four ribosomal RNA (rRNA) genes, 30 transfer RNA (tRNA) genes, as well as 78 protein-coding genes (PCGs). The cp genome organization, gene content and order in Argentina were highly conserved, but some visible divergences were present in IR/SC boundary regions. Ten regions (trnH-GUG-psbA, trnG-GCC-trnfM-CAU, trnD-GUC-trnY-GUA, rpl32-trnL-UAG, atpH-atpI, rps16-trnQ-UUG, trnS-GCU-trnG-UCC, ndhF-rpl32, trnR-UCU-atpA, and accD-psaI) were identified as excellent candidate DNA markers for future studies on species identification, population genetics and phylogeny of Argentina. Our results indicated that Argentina is monophyletic. In the current sampling, the A. smithiana -A. anserina clade was sister to the remainder of Argentina. Our results corroborated the previous taxonomic treatments to transfer A. phanerophlebia and A. micropetala from the genus Sibbaldia L. to Argentina. Our results showed close relationships among A. stenophylla, A. microphylla, A. taliensis, and A. tatsienluensis, congruent with previous studies based on the morphology of these species. rps15, rps16, rps19, rpl16, rpl20, rpl22, rpoA, rpoB, rpoC1, rpoC2, atpA, atpF, psbB, psbF, ndhA, ndhB, ndhC, ndhD, ndhF, rbcL, accD, ccsA, matK, ycf1, ycf2) were with sites under positive selection, and adaptive evolution of these genes might have played crucial roles in Argentina species adaptation to the harsh mountain environment. This study will facilitate future work on taxonomy, phylogenetics, and adaptive evolution of Argentina.